ANA structure analcime and preparation method thereof

By mixing and crystallizing NaY molecular sieve with template agent and water, ANA structure zeolite with spherical crystal morphology and high acid amount was prepared, which solved the problems of complex zeolite synthesis methods and poor molecular diffusion effects in the existing zeolite synthesis, and achieved more efficient molecular diffusion performance.

CN119911934AActive Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311435179.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02
Estimated Expiration
2043-10-31

AI Technical Summary

Technical Problem

The existing zeolite synthesis method has complex preparation process and harsh conditions, large crystal size, polyhedron in structure, low acid amount, and poor molecular diffusion effect.

Method used

ANA structure zeolite was prepared by mixing NaY molecular sieve as raw material and crystallizing it after mixing with template agent and water, with a spherical crystal morphology and high acid amount.

Benefits of technology

The preparation process is simplified, the crystal morphology of zeolite is improved, and the molecular diffusion performance is improved. It is suitable for small molecule acid catalytic reaction, small molecule gas adsorption separation, and ion adsorption purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119911934A_ABST
    Figure CN119911934A_ABST
Patent Text Reader

Abstract

The invention relates to analcime with an ANA structure and a preparation method of the analcime, the chemical molecular formula of a unit cell of the analcime with the ANA structure is Na < x > [SiyAlzO96], x is equal to 6-15, y is equal to 30-37, and z is equal to 10-16; the analcime with the ANA structure has a spherical crystal morphology. The analcime with the ANA structure disclosed by the invention has a spherical crystal morphology, shows excellent molecular diffusion performance, and has a good application prospect in the fields of small molecular acid catalytic reaction, small molecular gas adsorption separation, ion adsorption purification and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of inorganic material synthesis, and in particular, to an ANA structure analcime and a preparation method thereof. Background Art

[0002] Analcime is a rare natural mineral zeolite with an ANA type topological structure and a small microporous structure formed by highly twisted eight-membered rings (0.42×0.16nm) and six-membered rings and four-membered rings. As an important mineral resource, analcime has a unique pore structure and crystal chemical properties. It has good application prospects and development value in small molecule selective catalysis, ion adsorption reaction, ion exchange for water purification and contaminated soil remediation, fluorine-containing and heavy metal ion wastewater treatment, extraction of high-value trace metals from salt lake brine, and adsorption and storage of radioactive substances.

[0003] Compared with the shortcomings of natural analcime, such as low purity, high impurity content, and unstable chemical composition, artificially synthesized analcime has the advantages of high purity, complete crystal structure, chemical stability, and adjustable physicochemical properties, so it is convenient for large-scale use. In the existing methods for artificially synthesizing analcime, conventional silicon sources and aluminum sources can be used for hydrothermal synthesis, or fly ash, geopolymers, illite, coal gangue, etc. can be used as raw materials for synthesis. However, the preparation process of the existing methods is complicated and the conditions are harsh, and the size of the synthesized analcime crystals is relatively large, the structural morphology is generally polyhedral, the acid content is low, and the molecular diffusion effect is poor. Summary of the invention

[0004] The purpose of the present disclosure is to provide an ANA structure analcime and a preparation method thereof, so as to simplify the preparation process and improve the crystal morphology of analcime.

[0005] In order to achieve the above-mentioned object, the present disclosure provides, in a first aspect, an ANA structure analcime, wherein the unit cell chemical formula of the ANA structure analcime is |Na x |[Si y Al z O 96 ], wherein x=6-15, y=30-37, z=10-16; the ANA structure analcime has a spherical crystal morphology.

[0006] Optionally, the ANA structured analcime has a rough surface and a spherical crystal morphology with holes, and the diameter of the sphere is 2 to 10 μm.

[0007] Optionally, the total acid content of the ANA structure analcime is not less than 210 μmol·g -1 .

[0008] In a first aspect of the present disclosure, a method for preparing the ANA structure analcime described in the first aspect of the present disclosure is provided, the method comprising:

[0009] Mixing NaY molecular sieve, template and optional water to obtain an initial mixture;

[0010] The initial mixture is crystallized to obtain a crystallized product.

[0011] Optionally, the molar composition of the initial mixture is: SiO2 / Al2O3=2~10, NaOH / SiO2=0.2~0.6, R / SiO2=0.05~0.8, H2O / SiO2=5~40, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

[0012] Optionally, the molar composition of the initial mixture is: SiO2 / Al2O3=3~8, NaOH / SiO2=0.3~0.5, R / SiO2=0.1~0.5, H2O / SiO2=8~20, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

[0013] Optionally, the template is tetraethylammonium hydroxide.

[0014] Optionally, the crystallization conditions include: a temperature of 130 to 170° C. and a time of 40 to 80 hours.

[0015] Optionally, the crystallization conditions include: a temperature of 140 to 160° C. and a time of 45 to 75 hours.

[0016] Optionally, the method further comprises the steps of washing, filtering and drying the crystallized product, and optionally ammonium exchange treatment and calcination.

[0017] Through the above technical scheme, the present invention uses NaY molecular sieve as a raw material to synthesize ANA structure analcime, without adding inorganic base, and no aging or aging process is required before crystallization. The raw materials and preparation process are simple, and the production cost is low. The ANA structure analcime disclosed in the present invention has a spherical crystal morphology, shows excellent molecular diffusion performance, and has good application prospects in the fields of small molecule acid catalytic reaction, small molecule gas adsorption separation, ion adsorption purification, etc.

[0018] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0020] Figure 1 It is the XRD spectra of the NaY molecular sieve used in the embodiment and the ANA structure analcime synthesized in the embodiment and the comparative example;

[0021] Figure 2 is a SEM photograph of the NaY molecular sieve used in Example 1;

[0022] Figure 3 is a SEM photograph of the ANA structure analcime synthesized in Example 1;

[0023] Figure 4 is a SEM photograph of the ANA structure analcime synthesized in Example 2;

[0024] Figure 5 This is a SEM photograph of the ANA structure analcime synthesized in Example 3. DETAILED DESCRIPTION

[0025] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0026] In a first aspect, the present invention provides an ANA structure analcime, wherein the unit cell chemical formula of the ANA structure analcime is |Na x |[Si y Al z O 96 ], wherein x=6-15, y=30-37, z=10-16. The ANA structure analcime has a spherical crystal morphology, and further has a rough surface hole spherical crystal morphology. In one embodiment, the spherical diameter size can be 2-10 μm. The ANA structure analcime has a high acid content. In one embodiment, the total acid content of the ANA structure analcime is not less than 210 μmol·g -1 , for example, 210 to 400 μmol·g -1 .

[0027] In a second aspect of the present disclosure, a method for preparing the ANA structure analcime described in the first aspect of the present disclosure is provided, the method comprising:

[0028] Mixing NaY molecular sieve, template and optional water to obtain an initial mixture;

[0029] The initial mixture is crystallized to obtain a crystallized product.

[0030] The molar composition of the initial mixture is: SiO2 / Al2O3=2-10, NaOH / SiO2=0.2-0.6, R / SiO2=0.05-0.8, H2O / SiO2=5-40, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

[0031] In a preferred embodiment, the molar composition of the initial mixture is: SiO2 / Al2O3=3~8, NaOH / SiO2=0.3~0.5, R / SiO2=0.1~0.5, H2O / SiO2=8~20, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

[0032] The present disclosure has no special restrictions on the NaY molecular sieve, as long as it can meet the molar composition of the above-mentioned initial mixture (i.e., the NaY molecular sieve has SiO2 / Al2O3=2-10, NaOH / SiO2=0.2-0.6, preferably SiO2 / Al2O3=3-8, NaOH / SiO2=0.3-0.5), and can be a commercial product or prepared by conventional methods in the art.

[0033] The template may be tetraethylammonium hydroxide. The crystallization may be static or dynamic crystallization. The crystallization conditions may include: a temperature of 130 to 170° C. and a time of 40 to 80 hours. Preferably, the crystallization conditions include: a temperature of 140 to 160° C. and a time of 45 to 75 hours.

[0034] The method may also include the steps of washing, filtering and drying the crystallized product; further, the drying conditions may include: a temperature of 70 to 120° C. and a time of 6 to 12 hours, and after drying, ANA structure analcime raw powder may be obtained.

[0035] Furthermore, the method may also include: subjecting the ANA structure analcime raw powder to one or more ammonium exchange treatments (for example, stirring and mixing the ANA structure analcime, ammonium chloride, and deionized water in a weight ratio of 1:0.3:20, heating to 70°C and stirring for 2 hours), washing, filtering, and drying to obtain ammonium-type ANA structure analcime, and then calcining the ammonium-type ANA structure analcime (for example, calcining at 550°C for 3 hours) to obtain hydrogen-type ANA structure analcime.

[0036] The ANA structured analcime disclosed in the present invention has good application prospects in the fields of small molecule acid catalysis reaction, small molecule gas adsorption separation, and ion adsorption purification.

[0037] The present disclosure is further described below by way of examples, but the contents of the present disclosure are not limited thereby.

[0038] In the following examples, X-ray powder diffraction phase analysis (XRD) was performed using a PANalytical Empyrean diffractometer equipped with a PIXcel 3D Detector. Test conditions: Cu target, Kα radiation, Ni filter, tube voltage 40kV, tube current 40mA, scanning range 5~50°.

[0039] In the following examples, scanning electron microscope (SEM) morphology analysis was performed using a Japanese Hitachi S4800 scanning electron microscope. Test conditions: After the sample was dried and ground, it was glued on a conductive adhesive. The acceleration voltage of the analysis electron microscope was 5.0 kV, and the magnification was 20-800000 times.

[0040] In the following examples, the X-ray fluorescence analysis (XRF analysis) test instrument is Philips MagiX fluorescence spectrometer. Test conditions: tungsten target, excitation voltage 40kV, excitation current 50mA. The intensity of the characteristic spectrum line of each element is measured by a scintillation counter and a proportional calculator to perform element semi-quantitative analysis.

[0041] In the following examples, ammonia temperature-programmed desorption (NH3-TPD analysis) was performed using an AutochemⅡ2920 temperature-programmed desorber from Micromeritics, USA. Test conditions: 0.2 g of 20-40 mesh molecular sieve was weighed and loaded into a sample tube, which was placed in a thermal conductivity cell heating furnace, and He gas was used as the carrier gas (25 mL·min -1 ), at 20℃·min -1 The temperature was raised to 600℃ at a rate of 100℃, and the impurities adsorbed on the surface of the molecular sieve were removed by purging for 60 minutes. Then the temperature was lowered to 100℃, kept at a constant temperature for 10 minutes, and switched to NH3-He mixed gas (10% NH3 + 90% He) for adsorption for 30 minutes. Then, He gas was purged for 90 minutes until the baseline was stable to desorb the physically adsorbed ammonia. -1The temperature was raised to 600°C by a programmable heating rate for desorption and maintained for 30 min. The desorption was completed. The TCD detector was used to detect the changes in gas components, and the instrument automatically integrated to obtain the total acid content.

[0042] In the following examples, the testing instrument for BET analysis is Micromeritics ASAP 2010 adsorption instrument. Test conditions: The weighed sample is vacuumed to 1.33×10 -2 Pa, constant temperature and pressure for 15h, sample pretreatment. At liquid nitrogen temperature -196℃, the adsorption and desorption of nitrogen by the sample under different pressure ratios p / p0 were measured to obtain nitrogen adsorption-desorption isotherms. The BET specific surface area was calculated using the BET formula, and the micropore specific surface area and micropore volume of the sample were calculated using the t-plot method. The total pore volume was calculated using the adsorption at P / P0 = 0.98.

[0043] The NaY molecular sieve raw materials used in the following examples were purchased from Sinopec Petrochemical Research Institute Co., Ltd.

[0044] Example 1

[0045] The XRD spectrum of the NaY molecular sieve used in this example is shown in Figure 1 , SEM photos see Figure 2 The chemical composition of the NaY molecular sieve was analyzed by XRF, and its composition was Na2O 12.7% by weight, Al2O3 21.3% by weight, SiO2 65.7% by weight, Fe2O3 0.0826% by weight and other low-content impurities. The molar ratio of SiO2 / Al2O3 was calculated to be 5.234, and the molar ratio of NaOH / SiO2 was 0.375. The NaY molecular sieve was calcined in a muffle furnace at 550°C for 3 hours, and the solid content of the NaY molecular sieve was determined to be 74.10% by weight. BET analysis was performed, and its specific surface area was 732m 2 ·g -1 , the pore volume is 0.348 cm 3 ·g -1 .

[0046] Take 2.711 grams of deionized water and add it to the polytetrafluoroethylene lining, add 6.136 grams of tetraethylammonium hydroxide TEAOH (35% by weight) and stir evenly, then add 6 grams of NaY molecular sieve and stir evenly to obtain the molar composition of the initial mixture: SiO2 / Al2O3=5.234, NaOH / SiO2=0.375, TEAOH / SiO2=0.3, H2O / SiO2=10.

[0047] The polytetrafluoroethylene liner containing the initial mixture was sealed with a cover, placed in a rotary oven with a rotation speed set to 20 r / min, and crystallized at 155°C for 48 hours under autogenous pressure. After the crystallization was completed and cooled to room temperature, the product was taken out, filtered, washed, and dried at 80°C for 12 hours to obtain a solid sample (denoted as S1).

[0048] The obtained solid sample was subjected to X-ray diffraction analysis, and the XRD spectrum was shown in Figure 1 , and the XRD spectrum of the synthesized analcime in the literature (Microporous & Mesoporous Materials, 2005, 86 (1-3): 106-111.) Figure 1 The results show that it is pure ANA structure analcime. Figure 3 The structure is a spherical crystal with a rough surface and a spherical diameter of about 5.0 μm. XRF elemental analysis of the synthesized ANA structure analcite raw powder showed that its unit cell chemical formula is |Na 9.42 |[Si 34.61 Al 14.71 O 96 ].

[0049] The synthesized ANA structure analcime raw powder was subjected to ammonium exchange treatment. Analcime, ammonium chloride and deionized water were stirred and mixed in a weight ratio of 1:0.3:20, heated to 70°C and stirred for 2h, washed, filtered, and ammonium exchanged twice, and dried to obtain ammonium analcime, which was then calcined at 550°C for 3h to obtain hydrogen analcime. The acid content of hydrogen analcime was analyzed by NH3-TPD, and the total acid content was 234.1μmol·g -1 .

[0050] Example 2

[0051] Take 5.371 grams of deionized water and add it to the polytetrafluoroethylene liner, add 2.045 grams of tetraethylammonium hydroxide TEAOH (weight fraction 35%) and stir evenly, then add 6 grams of NaY molecular sieve the same as in Example 1 and stir evenly to obtain the molar composition of the initial mixture: SiO2 / Al2O3=5.234, NaOH / SiO2=0.375, TEAOH / SiO2=0.1, H2O / SiO2=10.

[0052] The polytetrafluoroethylene liner containing the initial mixture was sealed with a cover, placed in a rotary oven with a rotation speed set to 20 r / min, and crystallized at 145°C for 72 hours under autogenous pressure. After the crystallization was completed and cooled to room temperature, the product was taken out, filtered, washed, and dried at 80°C for 12 hours to obtain a solid sample (denoted as S2).

[0053] The obtained solid sample was subjected to X-ray diffraction analysis, and the XRD spectrum was shown in Figure 1 , is pure phase ANA structure analcime, SEM photo see Figure 4 The structure is a spherical crystal with a rough surface and a spherical diameter of about 2.4 μm. XRF elemental analysis of the synthesized ANA structure analcite raw powder showed that its unit cell chemical formula is |Na 10.32 |[Si 35.12 Al 13.73 O 96 ].

[0054] The synthesized ANA structure analcime raw powder was subjected to ammonium exchange treatment. Analcime, ammonium chloride and deionized water were stirred and mixed in a weight ratio of 1:0.3:20, heated to 70°C and stirred for 2h, washed, filtered, and ammonium exchanged twice, and dried to obtain ammonium analcime, which was then calcined at 550°C for 3h to obtain hydrogen analcime. The acid content of hydrogen analcime was analyzed by NH3-TPD, and the total acid content was 298.3μmol·g -1 .

[0055] Example 3

[0056] The ANA structure analcime was synthesized according to the method of Example 2, except that the amount of template added was TEAOH / SiO2=0.2.

[0057] The XRD spectrum of the obtained solid sample (denoted as S3) is shown in Figure 1 , which is pure phase ANA structure analcime. SEM photos are shown in Figure 5 The structure is a rough surface with a hole-shaped spherical crystal shape, and the sphere diameter is about 3.7 to 9.2 μm. XRF elemental analysis of the synthesized ANA structure analcite raw powder shows that its unit cell chemical formula is |Na 9.70 |[Si 35.01 Al 14.08 O 96 ].

[0058] Take the synthesized ANA structure analcime raw powder for ammonium exchange treatment, stir and mix analcime, ammonium chloride and deionized water in a weight ratio of 1:0.3:20, heat to 70℃ and stir for 2h, wash, filter, and perform ammonium exchange treatment twice, and dry to obtain ammonium analcime. Roast at 550℃ for 3h to obtain hydrogen analcime. The acid content of hydrogen analcime was analyzed by NH3-TPD, and its total acid content was 219.2μmol·g -1 .

[0059] Example 4

[0060] The ANA structure analcime was synthesized according to the method of Example 2, except that the amount of template added was TEAOH / SiO2=0.4, and the crystallization conditions were 145°C for 48 hours.

[0061] The XRD spectrum of the obtained solid sample (denoted as S4) is shown in Figure 1 , which is pure phase ANA structure analcime. SEM analysis confirmed that its structural morphology is a hole-spherical crystal with a rough surface, and the sphere diameter is about 4.3 to 7.1 μm. XRF element analysis of the synthesized ANA structure analcime raw powder showed that its unit cell chemical formula is |Na 10.17 |[Si 35.13 Al 13.77 O 96 ]. The acid content of hydrogen-type analcime was analyzed by NH3-TPD, and the total acid content was 305.7 μmol·g -1 .

[0062] Example 5

[0063] The ANA structure analcime was synthesized according to the method of Example 2, except that the crystallization condition was 130° C. for 40 hours.

[0064] The XRD spectrum of the obtained solid sample is similar to that of S1 to S4, which is pure phase ANA structure analcime. SEM analysis confirms that its structural morphology is a hole-spherical crystal morphology with a rough surface, and the sphere diameter is about 2.0 to 3.3 μm. XRF elemental analysis of the synthesized ANA structure analcime raw powder shows that its unit cell chemical formula is |Na 10.01 |[Si 34.67 Al 14.44 O 96 ]. The acid content of hydrogen-type analcime was analyzed by NH3-TPD, and the total acid content was 216.9 μmol·g -1 .

[0065] Example 6

[0066] The ANA structure analcime was synthesized according to the method of Example 2, except that the crystallization condition was 170° C. for 80 hours.

[0067] The XRD spectrum of the obtained solid sample is similar to that of S1 to S4, which is pure phase ANA structure analcime. SEM analysis confirms that its structural morphology is a hole-spherical crystal with a rough surface, and the sphere diameter is about 4μm. XRF elemental analysis of the synthesized ANA structure analcime raw powder shows that its unit cell chemical formula is |Na 10.47 |[Si 35.20 Al 13.57 O 96 ]. The acid content of hydrogen-type analcime was analyzed by NH3-TPD, and the total acid content was 217.8 μmol·g -1 .

[0068] Comparative Example 1

[0069] Take 10.765 grams of deionized water and add it to the polytetrafluoroethylene liner, add 3.257 grams of tetraethylammonium hydroxide TEAOH (weight fraction 35%) and stir evenly, then add 2 grams of NaY molecular sieve the same as in Example 1 and stir evenly, then add 4.053 grams of solid silica gel (SiO2 weight fraction 90.72%), and the molar composition of the initial mixture is: SiO2 / Al2O3=25, NaOH / SiO2=0.078, TEAOH / SiO2=0.1, H2O / SiO2=10.

[0070] The polytetrafluoroethylene liner containing the initial mixture was sealed with a cover, placed in a rotary oven with a speed set to 20 r / min, and crystallized at 155°C for 48 hours under autogenous pressure. After the crystallization was completed and cooled to room temperature, the product was taken out, filtered, washed, and dried at 80°C for 12 hours to obtain a solid sample (denoted as D1).

[0071] The obtained solid sample was subjected to X-ray diffraction analysis, and the XRD spectrum was shown in Figure 1 , which is a Y molecular sieve and cannot synthesize ANA structure analcime.

[0072] Comparative Example 2

[0073] Take 8.648 grams of deionized water and add it to the polytetrafluoroethylene liner, add 6.513 grams of tetraethylammonium hydroxide TEAOH (weight fraction 35%) and stir evenly, then add 2 grams of NaY molecular sieve the same as in Example 1 and stir evenly, then add 4.053 grams of solid silica gel (SiO2 weight fraction 90.72%), and the molar composition of the initial mixture is: SiO2 / Al2O3=25, NaOH / SiO2=0.078, TEAOH / SiO2=0.2, H2O / SiO2=10.

[0074] The polytetrafluoroethylene liner containing the initial mixture was sealed with a cover, placed in a rotary oven with a rotation speed set to 20 r / min, and crystallized at 145°C for 72 hours under autogenous pressure. After the crystallization was completed and cooled to room temperature, the product was taken out, filtered, washed, and dried at 80°C for 12 hours to obtain a solid sample (denoted as D2).

[0075] The obtained solid sample was subjected to X-ray diffraction analysis, and the XRD spectrum was shown in Figure 1 , which is a Y molecular sieve and cannot synthesize ANA structure analcime.

[0076] Comparative Example 3

[0077] Take 4.414 grams of deionized water and add it to the polytetrafluoroethylene liner, add 13.026 grams of tetraethylammonium hydroxide TEAOH (weight fraction 35%) and stir evenly, then add 2 grams of NaY molecular sieve and stir evenly, then add 4.053 grams of solid silica gel (SiO2 weight fraction 90.72%), and the molar composition of the initial mixture is: SiO2 / Al2O3=25, NaOH / SiO2=0.078, TEAOH / SiO2=0.4, H2O / SiO2=10.

[0078] The polytetrafluoroethylene liner containing the initial mixture was sealed with a cover, placed in a rotary oven with a rotation speed set to 20 r / min, and crystallized at 145°C for 48 hours under autogenous pressure. After the crystallization was completed and cooled to room temperature, the product was taken out, filtered, washed, and dried at 80°C for 12 hours to obtain a solid sample (denoted as D3).

[0079] The obtained solid sample was subjected to X-ray diffraction analysis, and the XRD spectrum was shown in Figure 1 , which is a mixed crystal phase of Y molecular sieve and beta molecular sieve, and cannot synthesize ANA structure analcime.

[0080] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0081] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0082] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. An ANA structure analcime, characterized in that: The unit cell chemical formula of the ANA structure analcime is |Na x |[Si y Al z O 96 ], wherein x=6-15, y=30-37, z=10-16; the ANA structure analcime has a spherical crystal morphology.

2. The ANA structure analcime according to claim 1, wherein The ANA structure analcime has a rough surface and a hole-spherical crystal morphology, and the diameter of the sphere is 2 to 10 μm.

3. The ANA structure analcime according to claim 1 or 2, wherein The total acid content of the ANA structure analcime is not less than 210 μmol·g -1 .

4. A method for preparing the ANA structure analcime according to any one of claims 1 to 3, characterized in that: The method includes: Mixing NaY molecular sieve, template and optional water to obtain an initial mixture; The initial mixture is crystallized to obtain a crystallized product.

5. The method according to claim 4, wherein: The molar composition of the initial mixture is: SiO2 / Al2O3=2-10, NaOH / SiO2=0.2-0.6, R / SiO2=0.05-0.8, H2O / SiO2=5-40, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

6. The method according to claim 4 or 5, wherein: The molar composition of the initial mixture is: SiO2 / Al2O3=3-8, NaOH / SiO2=0.3-0.5, R / SiO2=0.1-0.5, H2O / SiO2=8-20, wherein SiO2 represents the molar number of SiO2 contained in the NaY molecular sieve, Al2O3 represents the molar number of Al2O3 contained in the NaY molecular sieve, NaOH represents the molar number of NaOH contained in the NaY molecular sieve, R represents the molar number of the template, and H2O represents the molar number of water.

7. The method according to claim 4, wherein: The template agent is tetraethylammonium hydroxide.

8. The method according to claim 4, wherein: The crystallization conditions include: a temperature of 130 to 170° C. and a time of 40 to 80 hours.

9. The method according to claim 8, wherein: The crystallization conditions include: a temperature of 140 to 160° C. and a time of 45 to 75 hours.

10. The method according to claim 4, wherein: The method further comprises the steps of washing, filtering and drying the crystallized product, and optionally ammonium exchange treatment and calcination.

Citation Information

Patent Citations

  • Flaky mordenite molecular sieve as well as preparation method and application thereof

    CN115806300A

  • Water purifier for companion animal

    KR102459735B1

Cited By

  • In-situ crystal transformation preparation method and catalytic application of Nd-modified ANA molecular sieve

    CN120987341A

  • An in-situ transformation preparation method for Nd-modified ANA molecular sieves and its catalytic application.

    CN120987341B